Potensi Buah Nipah Tua (Nypa Fruticans Wurmb) Sebagai Bahan Pakan Ternak - Khalil Khalil; T. Hidayat (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
A field survey has been conducted to study the potency of fruit of palm grown in West Sumatra for animal feedstuff. Three coastal areas which were identified as most populated palm plant in West Sumatra were selected as study sites, i.e., Padang city and the districts of Padang Pariaman and Pesisir Selatan. Five clusters of palm were randomly selected in each selected site and then bunches of their fruit were identified. The bunches were divided into 4 groups based on maturity status: very young, young, mature and old fruit bunches. The old fruits were then harvested, weighed and processed to separate their endosperm part. After weighing, the endosperm were then dried and ground for chemical analysis. Parameters measured included: number of bunch, old fruit and their endosperm weigh, nutrient content of endosperm. The data were statistically analysis for variance analysis in completely block design with 3 treatments and 3 blocks as replicates. Results shown that the highest number of bunches was found by the old fruit (6.7 bunches/cluster), followed by the very young fruits (2.7), mature fruit (1.7) and young fruit (1.5). About 22 % of old fruit consisted of endosperm part. The endosperm contains about 16 % crude protein, very low crude fat of 0.6 %, but considerably high crude fiber of about 50.5 %.